EAEU Countries Foreign Trade Policy: Results of Simulation Modeling - A. B. Ginoyan; A. A. Tkachenko (Финансы: теория и практика)
The authors examine the impact of foreign trade on the development of the Eurasian Economic Union (EAEU). The relevance of the study is related to the role of foreign trade in the integration processes of the EAEU countries. The purpose of the study is to identify, on the basis of a modified gravity model of international trade, the possible contribution of changes in the foreign trade policy of the EAEU countries to the growth of their foreign trade. The authors apply a pseudo-maximum likelihood estimation method, which is Poisson regression. Based on the results of the gravity model, covering the data of 97 countries with volumes of 95% of world GDP and 85% of international trade flows, the authors identified the potential contribution of possible changes in the foreign trade policy of the EAEU countries to the growth of their foreign trade turnover, including the reorientation of country directions. The authors gave a quantitative assessment of the foreign trade potential of the EAEU countries in trade with the main partners. The study presents an assessment of the impact on the volume of foreign trade of Belarus of its possible accession to the WTO, which could increase this volume by 11.4%. Particular attention is paid to modeling the trade potential of the EAEU countries with 40 leading trading partners. An analysis of the foreign trade of these countries shows no noticeable changes in the structure of its directions, and the foreign trade turnover continues to grow at an insufficient rate. The simulation results led to the conclusion that the EAEU countries have significant trade potential with the United States, the United Arab Emirates, Singapore, Sweden, Malaysia, Spain and Brazil, and the actual volume of trade with these countries is less than 50% of the potential. Realization of this potential requires, as shown in the study, significant changes in the foreign economic orientation of the EAEU countries and modification of foreign trade policy.